The Impacts of Corvids on Biodiversity - Madden, Christine M (FitzPatrick Institute of African Ornithology, 2024)
Corvids are often referred to as efficient nest predators with potential negative impacts on biodiversity. Despite the plethora of literature focusing on the impact of corvids on their potential prey, no review has been conducted on the genus Corvus to synthesis these relationships, and to explore their likely impacts on biodiversity. This thesis conducts a systematic literature review on the impacts of corvids on biodiversity by collating information from two study types: experimental studies and correlative studies. The impacts of corvids were diverse and varied between studies, countries and species. The vast majority of studies were on impacts on birds, and of these passerines were the most frequently studied, followed by waders. Collating the results from both experimental and correlative studies revealed a negative impact for 29% (n=50) of cases, whereas no impact was detected in 63% (n=107) of cases, and I found a positive impact (suggesting a beneficial relationship) in 8% (n=13) of cases. Thus, from the studies that have been investigated, the main findings indicate that corvids most frequently have no detectable impact on target species, and that their impacts are certainly not consistently negative. Concerns of corvid impacts have been raised in South Africa, as one indigenous species, the pied crow (Corvus albus) seems to be increasing. The aim was to explore whether changes in pied crow abundance in South Africa correlate with certain covariates which have been suggested to be involved in their increase. These covariates include transmission lines, climate change (temperature and rainfall), and land cover. Using data from the South African Bird Atlas Project (SABAP) in two surveyed periods (SABAP1: 1987-1991; SABAP2: 2007-2012), I examined changes in pied crow reporting rates (a proxy for relative abundance), describing both the overall change between these time periods, and exploring whether these changes were associated with biomes, transmission lines, climate variables, or land cover. A significant overall increase in this proxy for pied crow abundance was found across South Africa in the last 25 years. Increases differed between different habitat types, with increases being greatest in shrublands and urban areas. A full model, including all the potential covariates, found significant relationships between both temperature and rainfall change, with reporting rates. Pied crows are increasing in regions that are becoming hotter and a little wetter, which are predominantly areas in the west and the interior. There were simultaneous decreases of pied crows in the eastern regions of the country. Thus, change appears to be operating at a broad scale associated with large-scale changes in climate (rainfall and temperature). These analyses represent the first attempt to quantify the changes in abundance and range shifts of pied crows in South Africa, and also represent one of the first studies in South Africa empirically to relate bird population changes to medium-term climate change data.